3D Assembly: Large‐Area 3D Hierarchical Superstructures Assembled from Colloidal Nanoparticles (Small 18/2019). Issue 18 (3rd May 2019) - Song, Guofen; Li, Jinghan; Yuan, Yang; Yao, Lulu; Gu, Jiajun; Liu, Qinglei; Zhang, Wang; Su, Yishi; Zhang, Di
Abstract : In article1805308, Jiajun Gu and co‐workers assemble nanosized metal and semiconductor building blocks with various sizes and shapes into hierarchical structures in centimeter size, by introducing steric hindrance to compensate for environmentally sensitive hydrogen‐bonds and electrostatic interaction.